Interferensi Bahasa Daerah Terhadap Pemakaian Bahasa Indonesia Siswa SDN Bulubonggu - Iskandar, Iskandar (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
The aim of this research is to find out what forms of regional language interference exist with students' Indonesian at SDN Bulubonggu. Data collection was carried out by conducting interviews and observations. The sample in this study was 30 people. Sampling was carried out using purposive sampling technique. The results show that there is still a lot of regional language interference with students' Indonesian at SDN Bulubonggu. These forms of interference result in the use of regional languages ​​which influence the use of Indonesian. The type of interference that occurs in students' speech acts is found in the field of linguistics, namely syntax.